I-DECIDE: A social prescribing and digital intervention protocol to promote sexual and reproductive health and quality of life among young Cape Verdeans - Costa, AS.; Mourão, S.; Santos, O.; Alarcão, V.; Virgolino, A.; Nogueira, P.; Bettencourt, M. R.; Reis, S.; Graça, A.; Henriques, A. (International Journal of Environmental Research and Public Health, 2021)
Cape Verdean governments have intensified the investment on the National Reproductive Health Program, aiming to provide universal and qualified services, especially to the youngest people. Nevertheless, data suggest that some health challenges remain in this group (e.g., high rates of early/unplanned pregnancies, illegal abortions, sexual risk behaviors). In this paper, we present a protocol of a community-based social prescribing and digital intervention to promote wellbeing and quality of life across the life course of young Cape Verdeans, with a specific focus on Sexual and Reproductive Health (SRH) related behaviors. The intervention program, to be developed in three years, will follow an Intervention Mapping approach, namely regarding needs assessment and study’s protocol. The program’s implementation and evaluation will occur simultaneously. The main expected result is the development of a sustainable training program implemented in coproduction with Cape Verdeans from Mindelo (in São Vicente island), with replicable potential in other Cape Verdean regions. The intervention will contribute to SRH-related literacy through the digital health literacy materials and to quality of life across the young’s life course.